O sentido da qualidade da educação : uma análise a partir do conceito de racionalidade em Habermas - Zanchin Junior, Mauro Celso (2017)
It is a fact the interference of strategic interests in education, in many cases reduced to the ‘middle’ condition for the achievement of political and economic ends. Because of this, the dissertation presents the communicative action as a proposal for reflection and delimitation of the existing interests between system and culture. Because it is a documentary research guided by a specific bibliography, we sought to develop the text through the analysis of the Habermasian bibliography, with the objective of extracting theoretical problematizations on the question of quality in education. Another methodological aspect was the interdisciplinary treatment of the theme with focus on education. Based on the literature review, we proposed the construction of a reference for pedagogical action in education, as follows: 1. to present the premise that for each type of reason there is a specific type of action: instrumental reason (paradigm of consciousness) proposes the so-called strategic action, guided by functional rules aimed at the success and effectiveness of action; and communicative reason (paradigm of intersubjectivity), in turn, proposes the communicative action, based on rules of symbolic interaction (debate) that aim at establishing criteria for mutual understanding (consensus). 2. To expose the instrumental dimension in the concept of quality in education, starting from an economistic vision. 3. Adapt Habermas’s theoretical framework to the field of education, especially his conception of communicative action, as a proposal for decolonization and re-signification of the mechanisms of social and systemic integration present in the school institution. Based on Habermas’s theory, we will take into account the hypothesis that communicative action can promote the potentialization of basic elements for democratic debate, with an end to understanding, in order to prevent the instrumental character of the unilateral constraints present in the procedures pedagogical and thus ensure learning that aim not only at market logic, but at the experience of normative interactions (referring to the social world) and expressive (referring to the subjective world).